2010
DOI: 10.1097/qad.0b013e32832ec1c3
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral treatment changes in adults from Côte d'Ivoire: the roles of tuberculosis and pregnancy

Abstract: Objective To determine the rates and causes of first antiretroviral treatment (ART) changes in HIV-infected adults in Côte d'Ivoire. Methods We evaluated adults who initiated ART in an outpatient clinic in Abidjan. We recorded baseline and follow-up data, including drug prescriptions and reasons for changing to alternative first-line regimens (drug substitution for any reason but failure) or second-line regimens (switch for failure). Results 2012 HIV-infected adults (73% women) initiated ART. At baseline, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

10
31
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 24 publications
(22 reference statements)
10
31
3
Order By: Relevance
“…However, tuberculosis was the only co-morbid diseases determined in this study, which triggered the regimen modification. This is in line with the study conducted in the UK [16] and Coited'lvoire [17].…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…However, tuberculosis was the only co-morbid diseases determined in this study, which triggered the regimen modification. This is in line with the study conducted in the UK [16] and Coited'lvoire [17].…”
Section: Discussionsupporting
confidence: 76%
“…Similarly, in the study conducted in Coited'lvoire [17] and Uganda [18], it was reported that treatment failure was one of the major reasons for discontinuation and modification of initial regimen.…”
Section: Discussionmentioning
confidence: 99%
“…These results are consistent with those found in our study. Similarly, the causes of change in treatment observed in our cohort are in accordance with those reported in Côte d'Ivoire [8]: ARV intolerance was the main cause of treatment changes with an incidence rate of 12.4/100 PY and over one third of these changes were due to pregnancy and tuberculosis.…”
Section: Hiv-1 and Hiv-d Infections (Comparing Hiv-2 Infection)supporting
confidence: 78%
“…In Côte d'Ivoire, an overall treatment change incidence of 20.7/100 PY has been reported for a median duration of 16.9 months [8]. In Mali, the incidence rate of ART changes was 16.2/100 PY for a median duration of 15 months [9].…”
Section: Hiv-1 and Hiv-d Infections (Comparing Hiv-2 Infection)mentioning
confidence: 99%
“…Côte d'Ivoire 16 and Swaziland 17 where AZT based ARV regimens accounted 49.8%, 42.42%, 42.0% and 37.9%, respectively.…”
mentioning
confidence: 99%